In Vivo Dosimetry Evaluation of External Photon Treatments of Brain, Pelvis and Breast Cancer with Diode Dosimeters - Alireza Mohammadkarim; Mahmoud Allahverdi; Mahbod Esfehani; Hasanali Nedaie; Alireza Shirazi (Basic & Clinical Cancer Research, 2016)
Background: Delivering the maximum dose to tumor while achieving the minimum dose delivery to normal tissue; is the most important goal in external radiotherapy. Diode in vivo dosimetry is widely considered to be an important tool for quality improvement of patient care in external radiotherapy. Uncertainty in dose delivery should fall within 5% of the prescribed dose as recommended by International Commission of Radiological Units and Measurement (ICRU). Materials and methods: In vivo dosimetry was implemented for treatments of 36 pelvis and 38 breast cancer patients which were treated by 60Co photon irradiation and 38 brain cancer patients which were treated by 6MV photon irradiation. The diode dosimeters that were used in this study were two different models of PTW products, T60010L model was used for 60Co photon beam and T60010M model was used for 6MV photon beams. Results: The frequency histograms of the relative difference between the expected and measured doses at breast, pelvis and brain treatments, have mean values and standard deviations of -1.21% ( 7.01%), -0.44% ( 4.06%) and -1.32% ( 5.08%) , respectively. Our study showed that the accurate prediction of the dose value at breast cancer treatment is harder than that at brain and pelvis cancer treatment and requires an estimation of the lack of scatter due to missing tissue. Conclusions: Quantitative verification of the prescribed daily dose is important in external radiotherapy to ensure precision in patient set-up accuracy in dose delivery.